Usability of Validated Sleep-assessment Questionnaires in Patients with Chronic Pruritus: An Interview-based Study - Theresa Suilmann; Claudia Zeidler; Nani Osada; Claudia Riepe; Sonja Ständer (Medical Journals Sweden, 2018)
Impaired sleep due to nocturnal pruritus is a common symptom in patients with chronic pruritus. However, there is no standardized, simplified instrument for assessing sleep-related problems in patients with chronic pruritus. After a literature search, we conducted 50 interviews with patients with chronic pruritus and tested 12 items most frequently used in routine sleep questionnaires. Afterwards, 2 sleep assessment questionnaires (Pittsburgh Sleep Quality Index; Regensburg Insomnia Scale) were selected for use in 88 patients with chronic pruritus with sleep impairment due to pruritus. They were completed twice; once before optimizing their individual pruritus therapy and once again after 4 weeks. During the latter survey, 21 patients reported that pruritus no longer negatively affected their sleep. These patients also achieved a significant improvement in their sleeping behaviour in the Regensburg Insomnia Scale. Therefore, the Regensburg Insomnia Scale appears to be well-suited to assessing sleep impairment in patients with chronic pruritus.